The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1371/journal.pntd.0010790
|View full text |Cite
|
Sign up to set email alerts
|

Arboviruses as an unappreciated cause of non-malarial acute febrile illness in the Dschang Health District of western Cameroon

Abstract: Acute febrile illness is a common problem managed by clinicians and health systems globally, particularly in the Tropics. In many regions, malaria is a leading and potentially deadly cause of fever; however, myriad alternative etiologies exist. Identifying the cause of fever allows optimal management, but this depends on many factors including thorough knowledge of circulating infections. Arboviruses such as dengue (DENV) cause fever and may be underdiagnosed in sub-Saharan Africa where malaria is a major focu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
62
0
12

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(74 citation statements)
references
References 74 publications
0
62
0
12
Order By: Relevance
“…The vector competence of Ae. aegypti [ 139 , 189 , 190 , 191 ] and Ae. albopictus [ 190 , 192 ] in the transmission of major arboviruses has been well-documented.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The vector competence of Ae. aegypti [ 139 , 189 , 190 , 191 ] and Ae. albopictus [ 190 , 192 ] in the transmission of major arboviruses has been well-documented.…”
Section: Resultsmentioning
confidence: 99%
“…as potential vectors of important viruses is still unknown. For the Culex mosquitoes already identified in studies of the Central African region, they have been frequently reported to be associated with zoonotic arboviruses such as RVFV and WNV [ 19 , 188 , 191 , 193 ]. Of the Culex spp.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, surveillance of arboviral etiologic pathogens related to common acute febrile illness is challenging, given that most attention has been given to the malaria response [7][8][9]. Second, there is limited availability of routine diagnostic procedures for Arbovirus screening and detection [10].…”
Section: Introductionmentioning
confidence: 99%
“…Mosquitoes are extensively studied due to their role in spreading viral and parasitic diseases of medical and zoonotic significance 1 . Over 3000 species of mosquitoes spread diseases like malaria, lymphatic filariasis and arboviruses 2,3 . The capital cities of Africa have been reported to be one of the hotspot areas for the spread of dangerous vector-borne diseases (VBDs) such as malaria 4 and arboviruses (chikungunya, dengue, Zika and yellow fever) 5 .…”
Section: Introductionmentioning
confidence: 99%